The Development of Nigerian Agriculture : suggestions for the future - Osuntogun, Adeniyi; Chasse, Philippe; Ugorji, Rex (Nigeria : Evans brothers (Nigeria publishers) Limited, 1986)
This book is made up of selected papers that were presented at the three symposia. Part 1 focuses on the problems of Nigerian Agriculture. Part 2 is concerned with crop and livestock Development. Part 3, the marketing of Nigerian Agricultural products is discussed. Part 4 is concerned with agricultural research and training etc.
Includes bibliographical references
hza 13/02/2019
Loans
Keywords: Agriculture; Nigeria